ปัจจัยคัดสรรที่มีความสัมพันธ์กับพฤติกรรมการใช้ยาตามเกณฑ์ของผู้ป่วยมะเร็งที่รักษาด้วยยาต้านมะเร็งชนิดรับประทานในโรงพยาบาลระดับตติยภูมิ - บุณฑ์ราตรีส์ วานิชรัตนกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This study was descriptive correlational research. The purposes were to describe medication adherence in cancer patients receiving oral anticancer agents in tertiary hospital and study relationships between selected factors; social support from family, perceived severity of symptoms, perceived severity of cancer, perceived benefit of treatment, beliefs about the necessity of medication, beliefs about the concern of medication and medication adherence. Multi-Stage sampling was used to recruit 121 cancer patients who received oral anticancer agents in 3 tertiary hospitals in Bangkok. The research instruments comprised of demographic data form, social support from family scale, perceived severity of symptoms scale, perceived severity of cancer scale, perceived benefit of treatment scale, beliefs about the necessity of medication scale, beliefs about the concern of medicine scale and medication adherence scale. The questionnaires were tested for their content validity index (CVI) by five experts. Their CVI were 0.95, 1.0, 1.0, 1.0, 1.0, 1.0, and 0.96, respectively. Their Cronbach’s alpha coefficients were 0.94, 0.92, 0.89, 0.89, 0.89, 0.77, and 0.82, respectively. Data were analyzed using frequency, percentage, mean, median, standard deviation, Pearson correlation coefficient. The results revealed that: 1. Medication adherence in cancer patients receiving oral anticancer agents was at good level (Mean = 4.50, SD = 0.36). 2. Social support from family and beliefs about the necessity of medicine were positively related to medication adherence in cancer patients at statistical significant level of .05(r = .40, and .24, respectively). In addition, beliefs about the concern of medicine was negatively related to medication adherence in cancer patients at statistical significant level of .05 (r = -.24). However perceived severity of symptoms, perceived severity of cancer and perceived benefit of treatment were not related to medication adherence in cancer patients (r = .04, .11, and .04 respectively, p > .05).